Stratigraphy, palaeomagnetism and age of volcanics in the upper regions of ÞJórsárdalur valley, central southern Iceland (Dataset) ... - LEÓ Kristjansson; ROBERT A. Duncan; ÁGÚST Gudmundsson (Magnetics Information Consortium (MagIC), 2023)
Paleomagnetic, rock magnetic, or geomagnetic data found in the MagIC data repository from a paper titled: Stratigraphy, palaeomagnetism and age of volcanics in the upper regions of ÞJórsárdalur valley, central southern Iceland ...